Tinjauan Yuridis terhadap Penegakan Tindak Pidana Terorisme Ditinjau dari â€œAsas Presumtion of Innocenceâ€ dan â€œPresumtion of Guiltâ€ - I Made Yogi Astawa; I Made Minggu Widyantara; Ni Made Sukaryati Karma (Jurnal Preferensi Hukum, 2020)
Terrorism is an act that uses violence or threat of violence. Thus, law enforcement against criminal acts of terrorism is carried out with the Indonesian Criminal Justice System, with the operation of criminal justice systems ranging from the level of investigation, prosecution, justice to Prisoners in Penitentiary institutions into a single unit of the criminal justice system that enforces legal rules related to criminal acts of terrorism based on the principles of "Presumtion of Innocence" and "Presumtion of Guilt". This study aims to determine the prevention of criminal acts of terrorism in terms of the principle of the Presumtion of Guilt and efforts to enforce criminal acts of terrorism in the perspective of the principle of the Presumtion of Innocence. This type of research is Normative research type. In this paper it can be concluded that the enforcement of criminal acts of terrorism can be done through preventive measures by preventing the first occurrence of criminal acts of terrorism and repressive efforts by carrying out law enforcement efforts against suspects or defendants of criminal acts of terrorism. The enforcement of criminal acts of terrorism based on the principle of the Presumtion of Innocence has been aligned and implemented with the criminal justice system and preceded by the existence of two pieces of initial evidence so that no procedural defects occur and result in human rights violations.